THE DESIGN, SIMULATION, AND MAKING MULTI CYCLONE AS DUST SEPARATOR EQUIPMENT - HUTAPEA (NIM : 13106092); Pembimbing, : Dr. Ir. Willy Adriansyah, FRESLY
Besides giving positive impact, industrial activity also gives negative impacts such as air pollution. Therefore, it is necessary to control air pollution through technology application using cyclone as a dust separator. There are some weaknesses that limit the use of cyclone, which is a relatively low efficiency for small particles, and the need of a large installation, especially an operation with a large capacity.To overcome these weaknesses, multicyclone is develeloped as a modification of the single cyclone. The goal of this final project is to design a multi-system cyclone, simulate the flow, construct the system and testing to see if this device is well-function. Other than that, the results of this test is as a reference to resolve a case in Industry. The software which is used in this simulation is CFD (Computational Fluids Dynamics) FLUENT 6.3.26. From the results of the simulation, the single cyclones maximum separation efficiency are 83% for the first material test and 84.4% for the second material test. The results of this test shows the value of multi-cyclone maximum separation efficiency is 89% for the first material test and 99% for the second material test. Both maximum value is obtained when the starting velocity is10.6 m/s, approaching the saltation velocity of a single cyclone which is 10.82 m/s. Based on the results, the conclusion is that for the same dimensions, multi cyclone has a higher separation efficiency than a single cyclone. This results has been used as a reference in resolving case in Cement Industry.